Book Reviews. Issue 1 (1st April 2018) - Bolton, Alexandra; Tichy, Amy
Creating Healing School Communities: School-Based Interventions for Students Exposed to Trauma, Catherine DeCarlo Santiago, Tali Ravi and Lisa H. Jaycox (2018) Washington, DC: American Psychological Association, 132 pp., ISBN-13 978-1-43382-862-1, p/bk, $44.95A Therapeutic Treasure Box for Working with Children and Adolescents with Developmental Trauma, Karen Treisman (2017) London: Jessica Kingsley Publishers, 424pp., ISBN 978-1-78592-263-3, h/bk, $39.95; ISBN 978-1-78450-553-0, e/bk, $39.95